Estrategias bioclimáticas para la vivienda autoconstruida en la urbanización Villa Pyme en Jamundí-Valle del Cauca. (2022)
Develop a methodological guide that compiles bioclimatic strategies for the improvement of self-built housing that improves the level of comfort urbanization villa pyme in Jamundí - Valle del cauca.